PEMANFAATAN LIMBAH PLASTIK MENJADI BARANG BERNILAI GUNA UNTUK MENINGKATKAN KREATIVITAS SISWA SEKOLAH DASAR DI KECAMATAN KOTO TANGAH KOTA PADANG - Ayunis Ayunis; Dicky Rustam; Leila Muhelni (LPPM Universitas Andalas, 2024)
Utilizing plastic waste as a material to create valuable goods has become an important topic in efforts to reduce the negative impact of plastic waste on the environment. However, not all schools understand and carry out activities to utilize plastic waste to become valuable goods. This activity explores the use of plastic waste to increase student creativity in elementary schools (SD) in Padang City. The aim of this activity is to provide elementary school students with knowledge and skills in utilizing plastic waste into valuable items and increase students' creativity. This activity was carried out at an elementary school in Koto Tangah District, Padang City, namely SDN 57 Air Cool. Activity methods include: (1) socialization; (2) training; (3) evaluation and mentoring. Data collection includes surveys and observations of students and teachers involved in creative activities using plastic waste. The research results show that creative use of plastic waste has encouraged students to develop creative skills, problem solving and environmental awareness. Through various activities such as crafts, fine arts, and science projects, students learn to turn plastic waste into useful and interesting products. Thus, integrating the use of plastic waste in the elementary school curriculum can be an effective strategy for increasing student creativity while teaching sustainable environmental values. So, the conclusion is that plastic waste can be used into valuable goods to provide a role important in children's development, especially in the development of students' attitudes and behavior in controlling the environment to create a green economy.